Preparation method and application of cobalt and nitrogen doped porous carbon oxygen reduction catalyst

Through the preparation method of cobalt and nitrogen doped porous carbon oxygen reduction catalyst, the problem of slow oxygen reduction kinetics of zinc-air batteries is solved, efficient and stable oxygen reduction performance is achieved, and the consumption of precious metals is reduced, and the advantage of high cost-effectiveness is high.

CN119812366APending Publication Date: 2025-04-11HEILONGJIANG UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510022145.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The oxygen reduction kinetics of zinc-air batteries are slow and existing electrocatalysts are expensive and unstable, limiting their large-scale applications.

Method used

The preparation method of cobalt and nitrogen-doped porous carbon oxygen reduction catalyst was used to prepare a highly active and stable catalyst by pyrolysis of adenine and composite salt and impregnation and adsorption strategies of cobalt salt solution.

Benefits of technology

The oxygen reduction performance comparable to that of precious metal catalysts is achieved, the half-wave potential reaches 0.877V, and the cycle stability is better than that of commercial Pt/C, reducing the consumption of precious metals, and has the advantages of low cost, high efficiency and good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812366A_ABST
    Figure CN119812366A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a cobalt and nitrogen doped porous carbon oxygen reduction catalyst, in particular to a preparation method and application of a cobalt and nitrogen doped porous carbon oxygen reduction catalyst. In order to solve the problem of slow oxygen reduction kinetics of a zinc-air battery, the invention designs an ORR electrocatalyst which is simple in preparation method, rich in pore content and high in active N concentration, and on the basis, an atom-dispersed Co-N-C efficient ORR catalyst containing Co-Nx active sites is prepared through an adsorption impregnation strategy. The electro-catalytic property of the transition metal-N-biomass carbon is improved to the maximum extent. As a cathode catalyst for assembling a zinc-air battery, the composite material shows application potential, and is applied to the technical field of catalyst preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a preparation method and application of a cobalt and nitrogen doped porous carbon oxygen reduction catalyst. Background Art

[0002] With the increasing demand for clean energy use, the development of efficient, cheap, and environmentally friendly energy conversion and storage devices has become more urgent. Zinc-air batteries have become the next generation of electrochemical energy storage power sources that have attracted much attention due to their much higher theoretical energy density than lithium-ion batteries. However, the development of zinc-air batteries faces a key factor: the slow oxygen reduction kinetics. Therefore, the development of practical electrocatalysts to improve the efficiency of the oxygen reduction reaction has become a major challenge. Although Pt-based ORR electrocatalysts are the most effective to date, their high price and instability limit their development in large-scale applications.

[0003] Biomass is an abundant, widespread and inexpensive resource. Carbon materials converted from biomass have many advantages, such as highly developed specific surface area, loose pore structure and good electrical conductivity, and are excellent electrode materials. During the pyrolysis process, the biomass precursor rich in heteroelements will dope its own heteroatoms into the carbon skeleton to adjust the surface properties of biomass-derived carbon materials. However, the heteroatoms themselves have problems such as poor ORR selectivity and insufficient stability. Therefore, there is an urgent need for a widely available and inexpensive electrocatalyst. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of slow oxygen reduction kinetics in zinc-air batteries and to provide a preparation method and application of a cobalt and nitrogen-doped porous carbon oxygen reduction catalyst.

[0005] The preparation method of a cobalt-nitrogen doped porous carbon oxygen reduction catalyst of the present invention is carried out according to the following steps:

[0006] 1. Preparation of SZ-NC-900

[0007] The adenine powder and the composite salt are mixed and ground, and then placed in a tube furnace for pyrolysis under protective gas, and the pyrolysis product is washed and dried to obtain SZ-NC-900;

[0008] 2. Doping with Cobalt Atoms

[0009] Dissolve CoCl2·6H2O and o-phenanthroline in anhydrous ethanol to obtain a Co-o-phenanthroline mixed solution at room temperature; add SZ-NC-900 prepared in step 1 to the Co-o-phenanthroline mixed solution, and stir magnetically at 60°C, and then pyrolyze under protective gas to obtain a cobalt- and nitrogen-doped porous carbon oxygen reduction catalyst; wherein the mass ratio of CoCl2·6H2O to SZ-NC-900 is 1-3:20.

[0010] The present invention utilizes adenine to design an ORR electrocatalyst with a simple preparation method, rich pore content, and high active N concentration. On this basis, a catalyst with excellent oxygen reduction performance is prepared through an adsorption impregnation strategy.

[0011] Beneficial effects of the present invention:

[0012] The present invention adopts an impregnation adsorption strategy to mix the cobalt salt solution with the prepared nitrogen-carbon material, thereby maximizing the oxygen reduction performance of the catalyst, and the half-wave potential E 1 / 2 =0.877V, making it comparable to precious metal catalysts, and the negative shift of the half-wave potential of CoNC-10 after 5000 cycles is only 38% of that of commercial Pt / C. It can not only be used in the oxygen reduction reaction of zinc-air batteries, but also reduce the consumption of precious metal-based catalysts. It has the advantages of low cost, high efficiency, good stability and high catalytic activity, and has important practical significance for accelerating the widespread application of energy storage devices such as zinc-air batteries and fuel cells in actual production and life. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 TEM image of SZ-NC-900 prepared by the present invention;

[0014] Figure 2 STEM image of CoNC-10 prepared by the present invention;

[0015] Figure 3 Roman diagrams of the electrocatalytic oxygen reduction materials CoNC-5, CoNC-10, and CoNC-15 prepared in Examples 1 to 3;

[0016] Figure 4 The fine spectra of various electrocatalytic oxygen reduction materials prepared by the present invention and the contents and distribution diagrams of different N species; wherein a is the Co2p fine spectrum, b is the C1s fine spectrum, c is the N1s fine spectrum, and d is the contents and distribution diagrams of different N species;

[0017] Figure 5 LSV diagrams of the electrocatalytic oxygen reduction materials CoNC-5, CoNC-10, and CoNC-15 prepared in Examples 1 to 3;

[0018] Figure 6The Tafel diagrams of the electrocatalytic oxygen reduction materials CoNC-5, CoNC-10 and CoNC-15 prepared in Examples 1 to 3;

[0019] Figure 7 CV comparison chart of CoNC-10 prepared in Example 2 and commercial Pt / C;

[0020] Figure 8 Accelerated durability curves of CoNC-10 prepared in Example 2 and commercial Pt / C;

[0021] Fig. 9 The power density and discharge polarization curves of CoNC-10 and commercial Pt / C prepared in Example 2 were applied to liquid zinc-air batteries and solid-state zinc-air batteries respectively;

[0022] Fig.10 The CoNC-10 prepared in Example 2 and the commercial Pt / C were respectively applied to the constant current discharge curves of liquid zinc-air batteries and solid-state zinc-air batteries at a certain current density. DETAILED DESCRIPTION

[0023] Specific implementation method 1: In this implementation method, a method for preparing a cobalt-nitrogen-doped porous carbon oxygen reduction catalyst is carried out according to the following steps:

[0024] 1. Preparation of SZ-NC-900

[0025] The adenine powder and the composite salt are mixed and ground, and then placed in a tube furnace for pyrolysis under protective gas, and the pyrolysis product is washed and dried to obtain SZ-NC-900;

[0026] 2. Doping with Cobalt Atoms

[0027] Dissolve CoCl2·6H2O and o-phenanthroline in anhydrous ethanol to obtain a Co-o-phenanthroline mixed solution at room temperature; add SZ-NC-900 prepared in step 1 to the Co-o-phenanthroline mixed solution, and stir magnetically at 60°C, and then pyrolyze under protective gas to obtain a cobalt- and nitrogen-doped porous carbon oxygen reduction catalyst; wherein the mass ratio of CoCl2·6H2O to SZ-NC-900 is 1-3:20.

[0028] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the composite salt described in step 1 is made by mixing NaCl and ZnCl2 in a mass ratio of 1:1. The rest is the same as the specific embodiment 1.

[0029] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the mass ratio of adenine powder to composite salt in step 1 is 1:10. The rest is the same as specific implementation method 1 or 2.

[0030] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that the protective gas in steps 1 and 2 is argon. The rest is the same as specific implementation methods 1 to 3.

[0031] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the pyrolysis described in step 1 refers to 5°C min -1 The heating rate is 900° C. for 1 hour. The rest is the same as that of the first to fourth embodiments.

[0032] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the mass ratio of CoCl2·6H2O to o-phenanthroline in step 2 is 1:2. The rest is the same as specific embodiments 1 to 5.

[0033] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the mass ratio of CoCl2·6H2O to SZ-NC-900 in step 2 is 1:10. The rest is the same as specific embodiments 1 to 6.

[0034] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the magnetic stirring is performed for 10 hours in step 2. The rest is the same as specific embodiments 1 to 7.

[0035] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the pyrolysis in step 2 is carried out at 5°C min -1 The heating rate is 800° C. for 1 hour. The rest is the same as that of the first to eighth embodiments.

[0036] Specific implementation method ten: This implementation method is an application of a cobalt and nitrogen doped porous carbon oxygen reduction catalyst in a zinc-air battery.

[0037] In this embodiment, cobalt and nitrogen doped porous carbon oxygen reduction catalyst is used as cathode catalyst of zinc-air battery.

[0038] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.

[0039] Embodiment 1:

[0040] A method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst is carried out according to the following steps:

[0041] 1. Preparation of SZ-NC-900

[0042] Adenine powder and composite salt were ground in an agate mortar at a mass ratio of 1:10; the mixture was placed in a tube furnace and pyrolyzed at 900 °C for 1 h with argon as protective gas at a heating rate of 5 °C min -1 The pyrolysis product was washed with deionized water and dried to obtain SZ-NC-900; wherein the composite salt was mixed with NaCl and ZnCl in a ratio of 5:5.

[0043] 2. Dissolve 5 mg CoCl2·6H2O and 10 mg o-phenanthroline in 20 mL anhydrous ethanol to generate a Co-o-phenanthroline complex at room temperature; add 100 mg SZ-NC-900 to the prepared Co-o-phenanthroline mixed solution and stir it magnetically at 60°C for 10 h. Finally, use argon as the protective gas and heat the mixture at 5°C min -1 The temperature was raised at 800 °C for 1 h to obtain CoNC-5 material.

[0044] The above CoNC-5 material was tested by linear sweep voltammetry (LSV) curve in the voltage range of -0.8 to 0.2 V using an electrochemical workstation in a three-electrode system (working electrode, cathode: glassy carbon electrode loaded with CoNC-5, counter electrode: platinum electrode, reference electrode: mercury / mercury oxide electrode), electrolyte: 0.1 M KOH (pH ≈ 13.2). Figure 5 .

[0045] Example 2

[0046] A method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst is carried out according to the following steps:

[0047] 1. Preparation of SZ-NC-900

[0048] Adenine powder and composite salt were ground in an agate mortar at a mass ratio of 1:10; the mixture was placed in a tube furnace and pyrolyzed at 900 °C for 1 h with argon as protective gas at a heating rate of 5 °C min -1 The pyrolysis product was washed with deionized water and dried to obtain SZ-NC-900; wherein the composite salt was mixed with NaCl and ZnCl in a ratio of 5:5.

[0049] 2. Dissolve 10 mg CoCl2·6H2O and 20 mg o-phenanthroline in 20 mL anhydrous ethanol to generate a Co-o-phenanthroline complex at room temperature; add 100 mg SZ-NC-900 to the prepared Co-o-phenanthroline mixed solution and stir it magnetically at 60°C for 10 h. Finally, use argon as the protective gas and heat the mixture at 5°C min -1 The temperature was raised at 800 °C for 1 h to obtain CoNC-10 material.

[0050] The above CoNC-10 material was tested by linear sweep voltammetry (LSV) curve in the voltage range of -0.8 to 0.2 V using an electrochemical workstation in a three-electrode system (working electrode, cathode: glassy carbon electrode loaded with CoNC-10, counter electrode: platinum electrode, reference electrode: mercury / mercury oxide electrode), electrolyte: 0.1 M KOH (pH ≈ 13.2). Figure 5 .

[0051] Figure 2 The STEM image of CoNC-10 prepared in this example shows that the C, N and Co elements are uniformly dispersed.

[0052] Example 3

[0053] A method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst is carried out according to the following steps:

[0054] 1. Preparation of SZ-NC-900

[0055] Adenine powder and composite salt were ground in an agate mortar at a mass ratio of 1:10; the mixture was placed in a tube furnace and pyrolyzed at 900 °C for 1 h with argon as protective gas at a heating rate of 5 °C min -1 The pyrolysis product was washed with deionized water and dried to obtain SZ-NC-900; wherein the composite salt was mixed with NaCl and ZnCl in a ratio of 5:5.

[0056] 2. Dissolve 15 mg CoCl2·6H2O and 30 mg o-phenanthroline in 20 mL anhydrous ethanol to generate a Co-o-phenanthroline complex at room temperature; add 100 mg SZ-NC-900 to the prepared Co-o-phenanthroline mixed solution and stir it magnetically at 60°C for 10 h. Finally, use argon as the protective gas and heat the mixture at 5°C min -1 The temperature was raised at 800 °C for 1 h to obtain CoNC-15 material.

[0057] The above CoNC-15 material was tested by linear sweep voltammetry (LSV) curve in the voltage range of -0.8 to 0.2 V using an electrochemical workstation in a three-electrode system (working electrode, i.e. cathode: glassy carbon electrode loaded with CoNC-15, counter electrode: platinum electrode, reference electrode: mercury / mercury oxide electrode), electrolyte: 0.1 M KOH (pH ≈ 13.2). Figure 5 .

[0058] Figure 1TEM image of SZ-NC-900 prepared in the above example; it shows that due to the etching effect of NaCl and ZnCl2, the material has many mesoporous (red circles) and microporous (white dots in the red frame magnified image) structures, and nitrogen is successfully doped into the carbon skeleton;

[0059] Figure 3 Roman diagrams of the electrocatalytic oxygen reduction materials CoNC-5, CoNC-10, and CoNC-15 prepared in Examples 1 to 3. When the amount of added Co salt increases from 5 mg to 10 mg, I D / I G It increased from 0.84 to 0.87, indicating that the defects of the material increased. When the amount of Co salt was increased to 15 mg, I D / I G It dropped from 0.87 to 0.85, indicating that the defects were reduced. Therefore, when the addition amount of Co salt was 10 mg, it was more conducive to introducing more defect sites into the NC skeleton;

[0060] Figure 4 Figure a is the high-resolution Co2p fine spectrum of CoNC. The peaks generated at 780.5eV and 795.7eV correspond to Co 3+ 2p 3 / 2 and Co 3+ 2p 1 / 2 , the peaks generated at 784 eV and 797.63 eV correspond to Co 2+ 2p 3 / 2 and Co 2+ 2p 1 / 2 The peaks generated at 790.4eV and 803.4eV correspond to Co 2+Characteristic satellite peaks. In addition to the above-mentioned common characteristic peaks, two peaks at 779.05eV and 793.6eV were observed from the Co2p fine spectrum of CoNC-15, which correspond to metal Co, indicating the presence of Co nanoparticles or clusters in CoNC-15. Figure b is the C1s fine spectrum of CoNC, which can be deconvoluted into CC (284.7eV), CN (285.7eV), CO (286.8eV) and C=O (289eV). The presence of CN bonds indicates that N atoms still exist in the porous carbon skeleton after secondary pyrolysis. Figure c is the N1s fine spectrum of CoNC, which can be deconvoluted into four peaks of 398.49eV, 399.52eV, 401.35eV and 403.93eV, which are assigned to pyridinic N, pyrrolic N, graphitic N and oxidized N, respectively. It is worth noting that with the increase in the amount of Co salt added, the pyridinic N content in CoNC decreased, while the graphitic N content increased (Figure d). A schematic diagram of the binding state of N in CoNC is shown in Figure d. Pyridinic N provides coordination sites for the Co atomic center to generate the Co-Nx part, while graphitic N affects the electronic structure of the carbon skeleton and improves the intrinsic ORR activity of the Co-Nx part. In addition, compared with CoNC-5 (75.66%) and CoNC-15 (72.21%), CoNC-10 has the most pyridinic N and graphitic N (79.21% in total), which indicates that CoNC-10 has potential high ORR activity.

[0061] Figure 5 LSV diagrams of the electrocatalytic oxygen reduction materials CoNC-5, CoNC-10, and CoNC-15 prepared in Examples 1 to 3. In 0.1 M KOH solution, CoNC-10 has a higher onset potential and half-wave potential (E onst 0.974V), E 1 / 2 =0.877dV), significantly better than commercial Pt / C (E onst =0.947V, E 1 / 2 =0.854V).

[0062] Figure 6 The Tafel plots of the electrocatalytic oxygen reduction materials CoNC-5, CoNC-10, and CoNC-15 prepared in Examples 1 to 3. CoNC-10 shows the lowest Tafel slope of 55.24 mV dec -1 , which indicates that CoNC-10 has a faster reaction rate and more active reaction kinetics in alkaline solution.

[0063] The specific redox performance index parameters of each sample material are shown in Table 1.

[0064] Table 1

[0065] Sample name Starting potential (V) Half-wave potential (V) Example 1 CoNC-5 0.952 0.866 Example 2 CoNC-10 0.974 0.877 Example 3 CoNC-15 0.911 0.819 Commercial Materials Pt / C 0.947 0.854

[0066] Based on the electrochemical parameters of starting potential, half-wave potential and limiting current density performance indicators, the salt ratio of the catalyst was studied. It can be seen from Table 1 that the starting potential follows the following order: CoNC-10>CoNC-5>Pt / C>CoNC-15.

[0067] The half-wave potentials follow the order as follows: CoNC-10>CoNC-5>Pt / C>CoNC-15.

[0068] It can be seen that the oxygen reduction activity of CoNC-10 obtained in Example 2 is the best.

[0069] Figure 7 This is a CV comparison diagram of CoNC-10 prepared in Example 2 and commercial Pt / C. It shows that CoNC-10 has a higher peak position and has excellent catalytic activity for ORR.

[0070] Figure 8 The accelerated durability curves of CoNC-10 and commercial Pt / C prepared in Example 2 show that after 5000 cycles in an oxygen-saturated 0.1M KOH solution, the half-wave potential of CoNC-10 only shifted negatively by 16 mV, while that of Pt / C catalyst shifted negatively by 42 mV, which is 2.6 times that of CoNC-10, indicating that the stability of CoNC-10 catalyst is better than that of Pt / C.

[0071] Fig. 9 The power density and discharge polarization curves of CoNC-10 and commercial Pt / C prepared in Example 2 were applied to liquid zinc-air batteries and solid-state zinc-air batteries, respectively. It shows that CoNC-10 catalyst has higher potential value and peak power density within a given voltage range, which are better than Pt / C.

[0072] Fig.10 The constant current discharge curves of CoNC-10 prepared in Example 2 and commercial Pt / C applied to liquid zinc-air battery and solid zinc-air battery at a certain current density. It shows that the liquid zinc-air battery assembled with CoNC-10 catalyst has a constant current density of 10 mA cm -2 It can work stably for 140h, and its discharge capacity is 815.2mAh gz n -1 , higher than the 776.8mAhgz of commercial Pt / C n -1 , indicating that CoNC-10 can provide high discharge efficiency for liquid zinc-air batteries. The assembled solid-state zinc-air battery -2It can work stably for 12 hours and has long-term durability. Its discharge specific capacity is higher than that of commercial Pt / C, indicating that CoNC-10 can provide high discharge efficiency for zinc-air batteries.

Claims

1. A method for preparing a cobalt- and nitrogen-doped porous carbon oxygen reduction catalyst, characterized in that The method is carried out according to the following steps:

1. Preparation of SZ-NC-900 The adenine powder and the composite salt are mixed and ground, and then placed in a tube furnace for pyrolysis under protective gas, and the pyrolysis product is washed and dried to obtain SZ-NC-900; 2. Doping with Cobalt Atoms Dissolving CoCl2·6H2O and o-phenanthroline in anhydrous ethanol to obtain a Co-o-phenanthroline mixed solution at room temperature; adding SZ-NC-900 prepared in step 1 to the Co-o-phenanthroline mixed solution, and magnetically stirring at 60° C., and then pyrolyzing under protective gas to obtain a cobalt- and nitrogen-doped porous carbon oxygen reduction catalyst; The mass ratio of CoCl2·6H2O to SZ-NC-900 is 1-3:

20.

2. The method for preparing a cobalt- and nitrogen-doped porous carbon oxygen reduction catalyst according to claim 1, characterized in that The composite salt described in step 1 is prepared by mixing NaCl and ZnCl2 in a mass ratio of 1:

1.

3. The method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst according to claim 1, characterized in that The mass ratio of adenine powder to the composite salt described in step 1 is 1:

10.

4. The method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst according to claim 1, characterized in that The protective gas in steps 1 and 2 is argon.

5. The method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst according to claim 1, characterized in that The pyrolysis described in step 1 refers to 5°C min -1 The heating rate was 900 °C for 1 h.

6. The method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst according to claim 1, characterized in that In step 2, the mass ratio of CoCl2·6H2O to o-phenanthroline is 1:

2.

7. The method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst according to claim 1, characterized in that In step 2, the mass ratio of CoCl2·6H2O to SZ-NC-900 is 1:

10.

8. The method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst according to claim 1, characterized in that In step 2, magnetic stirring was performed for 10 h.

9. The method for preparing a cobalt-nitrogen doped porous carbon oxygen reduction catalyst according to claim 1, characterized in that The pyrolysis in step 2 was carried out at 5 °C min -1 The heating rate was 800 °C for 1 h.

10. Use of the cobalt and nitrogen doped porous carbon oxygen reduction catalyst as claimed in claim 1 in a zinc-air battery.